Pengaruh Penambahan Saccharomyces cerevisiae pada Pakan terhadap Pertumbuhan Ikan Kakap Putih (Lates calcarifer) - I Made Budiarsana; Pande Gde Sasmita Julyantoro; Alfi Hermawati Waskita Sari; I Gusti Ngurah Permana (Current Trends in Aquatic Science, 2023)
White snapper (Lates calcarifer) is one of the marine aquaculture commodities in Indonesia, which has high economic value and fast growth. This study aims to investigate the influence of Saccharomyces cerevisiae addition into feed on the growth of white snapper (Lates calcarifer). The growth observed was the absolute length growth, the absolute weight, feed conversion ratio, survival, and specific growth rate. This research used experimental methods with complete randomized design non-factorials. White snapper (size 2-3 cm) was maintained for 30 days at a stocking density of 1500 Ind/m3. There were 2 treatments conducted, K treatment (control) and S treatment (pellet + Saccharomyces cerevisiae 100 ml/kg feed). Data analysis was done using t-test. The result showed that the addition of Saccharomyces cerevisiae resulted in decreasing of feed conversion ratio. The absolute length and weight, specific growth rate and survival were higher than the treatment without the addition of Saccharomyces cerevisiae, but not statistically different (p>0,05). The S treatment resulted in higher value of the feed conversion ratio (2,28), growth (7,21 cm/month), absolute weight growth (13,75 g/ month), the specific growth rate (11,92 % /day) and survival of (84,07 % /month). Water quality values such as temperature ranged from 29-31,6 OC salinity 27-32 ppt, pH 7,11-7,57, and dissolved oxygen 1,74-5,64 ppm.